Medical Student’s Perception of Role Plays as an Effective TeachingLearning Strategy for a Complex Topic in Biochemistry - Sridevi Visvanathan; Gokulshankar S; Sethuraman KR (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: Biochemistry is considered a tough subject by many students as the complex biochemical processes and metabolic pathways are difficult to comprehend and remember. The objective of the study was to assess the effectiveness of role play as a teaching strategy in conveying the complex concepts of biochemistry to year-1 medical students. Methods: An academic role-play was conducted after an initial briefing of relevant facts and concepts of lipoprotein metabolism related to the kinetics of chylomicron. The role play was conducted for around 40 minutes and at the end of the session, a pre-validated questionnaire was provided to the students to give feedback. The questionnaire comprised of close-ended (using a 5point Likert scale) and open-ended questions to obtain their opinion on the effectiveness of role play as a teaching-learning method for biochemical concepts. Results: In this study, 87.5% of the students agreed or strongly agreed that the role play enriched their learning experience; 72.9% supported this teaching-learning strategy and stated that the role play helped them to visualize a mind map and recall the concepts better. 79% of the students felt that role play avoids boredom in the class. Discussion and conclusion: The present study attempted a creative and innovative use of role play to help students learn chylomicron kinetics in a large group setting. In the current role-play, the different regions of the whole lecture theatre served as different characters or components involved in the kinetics of chylomicrons. This idea of personification and anthropomorphism used in the role-play of lipoprotein metabolism are unique and novel. The feedback from the students revealed it to be more engaging and effective than a didactic lecture.